Influence of Storage Conditions on the Stability of Vitamin D3 and Kinetic Study of the Vitamin Degradation in Fortified Canola Oil during the Storage - Mina Zareie; Azam Abbasi; Shiva Faghih (Journal of Food Quality)
Nowadays, fortified vegetable oils with vitamin D3 are widely available in different countries. In this study, the influence of storage conditions including light, air, storage temperature, and time on vitamin D3 retention in fortified canola oil was evaluated. Moreover, a kinetic study on vitamin D3 degradation in the oil was done. To this aim, fortified canola oil was prepared at two initial concentrations of 6.87 mg·kg−1 and 13.8 mg·kg−1 and then filled in transparent and dark-brown polyethylene terephthalate bottles at two filling levels of 50% and 100%. Samples were kept in two temperatures of 4°C and room temperature (27°C). The retention of vitamin D3 in different samples showed that the vitamin content was affected by the packaging type, storage temperature, and initial concentration. Vitamin D3 in the samples with a lower concentration of the vitamin which was stored in the refrigerator showed the highest retention (91%) after 70 days of storage, and the samples with higher initial concentration packed in transparent containers which were stored at room temperature (RT) showed the greatest loss (55.6%). Results of the kinetic study also showed that vitamin D3 was affected by storage condition. The half-life of the vitamin D3 differed from 96 to 577 days depending on the storage condition.